Reconstructing the Chernobyl Nuclear Power Plant (CNPP) accident 30 years after. A unique database of air concentration and deposition measurements over Europe. (September 2016) - Evangeliou, Nikolaos; Hamburger, Thomas; Talerko, Nikolai; Zibtsev, Sergey; Bondar, Yuri; Stohl, Andreas; Balkanski, Yves; Mousseau, Timothy A.; Møller, Anders P.
Abstract: 30 years after the Chernobyl Nuclear Power Plant (CNPP) accident, its radioactive releases still remain of great interest mainly due to the long half-lives of many radionuclides emitted. Observations from the terrestrial environment, which hosts radionuclides for many years after initial deposition, are important for health and environmental assessments. Furthermore, such measurements are the basis for validation of atmospheric transport models and can be used for constraining the still not accurately known source terms. However, although the "Atlas of cesium deposition on Europe after the Chernobyl accident" (hereafter referred to as "Atlas") has been published since 1998, less than 1% of the direct observations of 137 Cs deposition has been made publicly available. The remaining ones are neither accessible nor traceable to specific data providers and a large fraction of these data might have been lost entirely. The present paper is an effort to rescue some of the data collected over the years following the CNPP accident and make them publicly available. The database includes surface air activity concentrations and deposition observations for 131 I, 134 Cs and 137 Cs measured and provided by Former Soviet Union authorities the years that followed the accident. Using the same interpolation tool as the official authorities, we have reconstructed a deposition map of 137 Cs based on about 3% of the data used to create the Atlas map. The reconstructed deposition map is very similar to the official one, but it has the advantage that it is based exclusively on documented data sources, which are all made available within this publication. In contrast to the official map, our deposition map is therefore reproducible and all underlying data can be used also for other purposes. The efficacy of the database was proved using simulated activity concentrations and deposition of 137 Cs from a Langrangian and a Euleurian transport model. Graphical abstract: Gridded map of the updated 137Cs deposition database for the Chernobyl accident. The resolution was set to 0.1° over Europe and 0.01° inside the Exclusion Zone of Chernobyl (25E-40E and 47N-55N). Highlights: A Chernobyl dataset is presented emphasising to the Former Soviet Union countries. Deposition data of 137 Cs have been improved significantly. A gridded database of 0.1° × 0.1° resolution over Europe is directly available. Using the same tools we have created a deposition map similar to Atlas. Deposition of 137 Cs, 90 Sr, 238 − 240 Pu and 241 Am from 2015 are included. Abstract : An extended dataset of Chernobyl observations is made publicly available with emphasis in the Former Soviet Union countries, where about half of the radioactive pollution occurred.